Optimization of therapy in secondary progressive multiple sclerosis - A. N. Boyko; S. K. Zyryanov; Ya. V. Vlasov (Неврология, нейропсихиатрия, психосоматика)
The article provides an analysis of modern methods of treatment of secondary progressive multiple sclerosis (SPMS). The only drug that has proven its effectiveness in all types of SPMS (with exacerbations and without exacerbations) is siponimod. Clinical trials of this drug have proven its efficacy and safety in this type of MS. If the drug is included in the list of high-cost technologies, this modern method of treating SPMS can be made available to all patients who need it.